The effect of special strength exercises for the deep trunk muscles in some body angles for the front hand spring on the floor exercises apparatus for young players (Journal of the College of Basic Education, 2024)
Through the contact of the researcher with those concerned with the sport of gymnastics, he sensed a weakness in the performance of the kinematic variables, especially the angles of work to perform the movement of the front hand spring on the floor exercises movements, as one of the basic movements that share its work with movements of more accuracy and requirements. Research folow The experimental method was conducted on the research sample, whose number is (6) players of the Iraqi team for artistic gymnastics, the youth category, between the ages of (13-15 years), and the pre-test and video imaging were conducted, and the biomechanical variables that were chosen by the experts of the game and kinesiology were extracted, after completing (8 weeks) of the proposed training program, then the variables and results were processed statistically, and the researcher came out with a set of conclusions. The researcher recommended the adoption of a training program prepared according to some biomechanical variables